How ESG Disclosure Affects Financial Performance - Alim Matur Rosyidah; Rizdina Azmiyanti (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The market is increasingly sustainability-focused, with ESG disclosures enhancing corporate transparency, investor trust, and long-term value. Specific Background: In Indonesia's consumer non-cyclicals sector, ESG disclosure’s impact on financial performance remains inconsistent. Knowledge Gap: Most studies use composite ESG indices, overlooking the separate impacts of each dimension, research analyzing these individually in Indonesia remains limited. Objective: This study analyzes the effect of environmental, social, and governance disclosure on the financial performance of non-cyclical companies on the IDX 2022–2024. Method: Using quantitative methods used secondary data from annual reports, sustainability reports, and Bloomberg with a sample of 18 companies (54 observations) using purposive sampling and regression analysis on panel data using EViews 13. Results: The results indicate that social and governance disclosure has a positive and significant influence on financial performance while environmental disclosure does not have a significant influence. Novelty: This study indicates that positive impacts only come from social aspects with governance so that it can clarify the influence on each dimension previously covered in composite ESG. Implications: These results can provide a lesson for managers and investors that social and governance aspects have a stronger financial impact than environmental aspects.